ENGLISH LEARNING STYLES BASED ON GENDER USED BY THE STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM OF UNIVERSITAS BENGKULU - Ferly Wahyuni; Syafrizal S; Syafryadin Syafryadin (Lingua Scientia, 2023)
This research was aimed at investigating the English learning style preferences used by female and male students in. It was designed as quantitative research with a survey method. Data were gathered by using a perceptual learning style preferences questionnaire that was adapted from Reid (1984). It had been validated by experts and it had been tried out to other respondents who had the same characteristics as the respondents in this present study to get the reliability of the questionnaire. A total sampling technique was used to involve 115 students of the third-semester of the English education study program of Universitas Bengkulu in the academic year of 2021-2022 in filling in the questionnaire, consisting of 28 male and 87 female students. The results show that the female students used three major learning styles (visual, auditory, and kinesthetic), two minor learning styles (tactile and group), and a negative learning style (individual). The most dominant learning style used by the female student was kinesthetics. Moreover, the male students used five major learning styles (visual, auditory, kinesthetic, tactile, and group), while the individual learning style was negative. The most dominant learning style used by the male students was the group. In conclusion, there is a different English learning styles between female and male students used by the third-semester students of the English education study program of Universitas Bengkulu in the academic year of 2021- 2022. The female students used three types of English learning style preferences, namely visual, auditory, and kinesthetic. Those English learning styles are major learning styles. Meanwhile, tactile and group learning styles are minor learning styles, and individual learning style is a negative learning styles for female students. The most dominant of the English learning styles used by them is kinesthetics. Further, male students used four types of English learning styles, namely visual, auditory, kinesthetics, and group. Those English learning styles are major learning styles. Meanwhile, individual learning style is a negative learning style for male students. The most dominant of the English learning styles used by them is the group. Keywords: learning styles, characteristic, gender, differences, group